Pengaruh Kualitas Produk dan Brand Image Terhadap Loyalitas Konsumen Mie Instan Indomie di Jakarta Utara - Agnes Monica Liesay; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
The hypothesis that emerges from this framework is that product quality and brand image each have a significant positive effect on consumer loyalty. In conducting this research, the object of research is Indomie consumers in North Jakarta. The sample taken as many as 123 respondents. This study uses a quantitative approach with purposive sampling technique method. Data was collected by distributing questionnaires using a Likert scale to measure each question. The data analysis technique used validity and reliability test, as well as multiple regression analysis. The data is processed using SPSS 20. The results of the analysis show that product quality and brand image have a significant positive effect on consumer loyalty. Thus it can be stated that the better the quality of the product, the more consumer loyalty will be. Indomie instant noodle product.